An overview of the effects of nanoplastics on marine organisms - Mohd Zaki, Muhammad Rozaimi; Aris, Ahmad Zaharin (Elsevier, 2022)
The ubiquity and detrimental effects of plastics in the environment have become global environmental concerns over the past decade. Intensive anthropogenic activities, such as urbanisation, industrialisation and increasing population density, have resulted in increased plastic pollution in the environment. Recently, nanoplastics have received increased research attention and concern because of their potential adverse effects on marine organisms. However, the potential ecological issues associated with nanoplastics are not yet fully understood because of the insufficient and limited research conducted to date on baseline data, exposure and associated risks for marine organisms. This review highlights an understanding of the nature and characteristics of nanoplastics, as well as the occurrence of nanoplastics in the marine environment. In the future, the effects of nanoplastics on marine organisms may directly or indirectly influence human health. Thus, this review also highlights the effects of nanoplastics on marine organisms. An overview and insights into the occurrence of nanoplastics in marine environments and their potential effects on marine organisms will facilitate the preventative interventions and measures of nanoplastics pollution in the marine environment.